Bacterial diet affects the age-dependent decline of associative learning in Caenorhabditis elegans - Satoshi Higurashi; Sachio Tsukada; Binta Maria Aleogho; Joo Hyun Park; Yana Al-Hebri; Masaru Tanaka; Shunji Nakano; Ikue Mori; Kentaro Noma (eLife, 2023)
The causality and mechanism of dietary effects on brain aging are still unclear due to the long time scales of aging. The nematode Caenorhabditis elegans has contributed to aging research because of its short lifespan and easy genetic manipulation. When fed the standard laboratory diet, Escherichia coli, C. elegans experiences an age-dependent decline in temperature–food associative learning, called thermotaxis. To address if diet affects this decline, we screened 35 lactic acid bacteria as alternative diet and found that animals maintained high thermotaxis ability when fed a clade of Lactobacilli enriched with heterofermentative bacteria. Among them, Lactobacillus reuteri maintained the thermotaxis of aged animals without affecting their lifespan and motility. The effect of Lb. reuteri depends on the DAF-16 transcription factor functioning in neurons. Furthermore, RNA sequencing analysis revealed that differentially expressed genes between aged animals fed different bacteria were enriched with DAF-16 targets. Our results demonstrate that diet can impact brain aging in a daf-16-dependent manner without changing the lifespan.